Determinants of productivity among senior citizens in Marikina City - De Guzman, Ines A.; Juadiong, Lilian L. (2008)
This exploratory study was conducted to identify the variables that are possible determinants of productivity among senior citizens in Marikina City and to develop a productivity-scoring instrument. The respondents were 354 male and female senior citizens aged 60-79 from Barangka and Concepcion Uno/Tumana, Marikina City. Data gathering was done using a researcher-made survey questionnaire, which consisted of three parts of combined checklist and fill-in type questions. Results show that only life activities such as walking, managing money, shopping for own groceries/personal items, using public transportation, cooking, home decorating, ironing, caring for infants/children, washing clothes using washing machine, washing clothes by hand, and washing the dished are the only specific indicators based on Havighurst's paradigm that predict productivity among senior citizens. Two models of productivity were developed based on the results. The first model is a 14-Predictor Productivity Model which includes 14 variables such as employment status, preparation for old age, walking, managing own money, shopping for groceries/personal items, riding public transport, washing clothes using washing machine, washing clothes by hand, washing the dishes, and volunteer work. The second model is an 11-Predictor Productivity Model, which includes all the variables in the 14-Predictor Productivity Model except employment status, preparation for old age, and volunteer work. It was generated using a p-value of α=.05. It has an accuracy of 93 percent. A productivity-scoring instruments was formulated for this model using the questions on the research questionnaire. The focus group discussion, using 20 participants who were not among the research respondents from the two barangays, validated the findings of the study.
Keywords: Older people -- Marikina City; Older people's conduct of life